I can't find a proper formula for this considering it's almost exclusively made up of implications. Can somebody help me?
EDIT: Sorry, I'm new to this site and still learning to use it. I've tried writing (P → Q) as (¬P ∨ Q) and then applying the distibutive laws but I feel like I've reached a dead end.
P -> q
is the same as no(p) OR q
If you replace, in your expression :
P -> (P -> Q)
is the same as no(P) OR (no(P) OR Q)
no(P) -> P (P -> (P -> Q))
is the same as no(no(p)) OR (no(P) OR (no(P) OR Q))
which is the same as p OR no(P) OR no(P) OR Q
which is always true ( because p or no(p) is always true)